Chemical Biology Gateways to Mapping Location, Association, and Pathway Responsivity - Long, Marcus J. C.; Liu, Xuyu; Aye, Yimon (Frontiers in Chemistry, 2019)
Here we discuss, how by applying chemical concepts to biological problems, methods have been developed to map spatiotemporal regulation of proteins and small-molecule modulation of proteome signaling responses. We outline why chemical-biology platforms are ideal for such purposes. We further discuss strengths and weaknesses of chemical-biology protocols, contrasting them against classical genetic and biochemical approaches. We make these evaluations based on three parameters: occupancy; functional information; and spatial restriction. We demonstrate how the specific choice of chemical reagent and experimental set-up unite to resolve biological problems. Potential improvements/extensions as well as specific controls that in our opinion are often overlooked or employed incorrectly are also considered. Finally, we discuss some of the latest emerging methods to illuminate how chemical-biology innovations provide a gateway toward information hitherto inaccessible by conventional genetic/biochemical means. Finally, we also caution against solely relying on chemical-biology strategies and urge the field to undertake orthogonal validations to ensure robustness of results.